Propagation Characteristics of Oblique Incident Terahertz Wave in Nonuniform Dusty Plasma - Yunhua Cao; Haiying Li; Zhe Wang; Zhensen Wu (International Journal of Antennas and Propagation)
Propagation characteristics of oblique incident terahertz wave from the nonuniform dusty plasma are studied using the propagation matrix method. Assuming that the electron density distribution of dusty plasma is parabolic model, variations of power reflection, transmission, and absorption coefficients with frequencies of the incident wave are calculated as the wave illuminates the nonuniform dusty plasma from different angles. The effects of incident angles, number density, and radius of the dust particles on propagation characteristics are discussed in detail. Numerical results show that the number density and radius of the dust particles have very little influences on reflection and transmission coefficients and have obvious effects on absorption coefficients. The terahertz wave has good penetrability in dusty plasma.